PENGARUH WORK-FAMILY CONFLICT DAN BEBAN KERJA TERHADAP STRES KERJA PEGAWAI PADA UPTD. PELAYANAN TRANSPORTASI DARATDINAS PERHUBUNGAN DENPASAR - Kartini, Ni Ketut Ayu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The transportation system has a vital role in regional development, especially in Denpasar City. UPTD. Land Transportation Services Transportation Departement Denpasar is a government organitation that oversees this field, so to produce good service, need employees with good mentalality, including not experiencing work stress. This research aims to determine the effect of work-family conflict and workload on employee work stress at UPTD. Land Transportation Services Transportation Departement Denpasar. The data analysis technique used is multiple linear regression analysis. The research results show that work-family conflict and workload have a positive and significant effect on work stress, both partially and simultaneously. This means that the higher level of work-family conflict and workload, the level of employee work stress at UPTD. Land Transportation Services Transportation Departement Denpasar will also be higher, and vice versa.